THE IMPACTS OF THE INVESTMENTS IN AGRICULTURE ON ECONOMIC GROWTH IN RURAL COMMUNITIES IN ROMANIA - Petre, Ionut Laurentiu; Ion, Raluca Andreea (Economics of Agriculture, 2019)
This paper seeks to analyze the impact of agricultural investments on economic growth in rural communities in Romania. It answers the question: are the investments in agriculture a determinant of economic growth in rural communities, and if yes, what is their impact on economic growth? The objectives are to identify, through linear regression models, the intensity and meaning of the relationships between the value of investments and the main indicators that can express economic growth in rural areas. In this purpose, the level of relationships between the value of investments in agriculture and the value of GDP in predominantly rural areas, the value of GDP in agriculture and the value of the agricultural production are analyzed. The main results show that the variables chosen are influenced by the value of the investments in different proportions, so the hypothesis that investment in agriculture has a positive and medium impact on rural economic growth is true. The most significant relationship is obtained between the value of agricultural investments and the value of agricultural production.